Parenting in Puerto Rican Families: Mothers and Father’s Self-Reported Practices - Domenech Rodríguez, Melanie M; Franceschi Rivera, Natalie; Sella Nieves, Zulma; Félix Fermín, Jahaira (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Little information is available on parenting practices of families living in Puerto Rico. In order to fill this gap, 55 two-parent families with a 6 to 11 year old child were surveyed on contextual stressors known to impact parenting (i.e., depression, subjective economic status, parenting stress, marital satisfaction), parenting practices (i.e., skills building, positive involvement, problem solving, monitoring, and effective discipline), as well as child externalizing behavior problems. Data reveal a sample with relatively low self-reported stressors, high endorsement of parenting practices, and subclinical child externalizing behaviors. All measures were reliable, indicating potential for future use in Puerto Rican samples. All relationships were in the expected direction between parenting practices and contextual stressors where higher reports on stressors were negatively related to endorsement of parenting practices. Similarly parenting practices negatively related to problematic scores in child outcomes. Maternal problem solving fully mediated the relationship between marital satisfaction and child externalizing behaviors. While substantive findings are reported, the research led t the formulation of many more questions than it answered. Implications for future research are provided.